2022
DOI: 10.48550/arxiv.2204.09177
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lie Algebraic Cost Function Design for Control on Lie Groups

Abstract: This paper presents a control framework on Lie groups by designing the control objective in its Lie algebra. Control on Lie groups is challenging due to its nonlinear nature and difficulties in system parameterization. Existing methods to design the control objective on a Lie group and then derive the gradient for controller design are non-trivial and can result in slow convergence in tracking control. We show that with a proper left-invariant metric, setting the gradient of the cost function as the tracking e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 22 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…The detailed proof of the theorems are presented in the work of Teng et al (2022b). For the proposed MPC, we can follow the same steps and estimate the region of attraction.…”
Section: Stability Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed proof of the theorems are presented in the work of Teng et al (2022b). For the proposed MPC, we can follow the same steps and estimate the region of attraction.…”
Section: Stability Analysismentioning
confidence: 99%
“…The experimental results confirm that the proposed approach provides faster convergence when rotation and position are controlled simultaneously. Future work will implement the trajectory optimization using this geometric control framework proposed by Teng et al (2022b) for robot control. Another interesting research direction is to incorporate learning into this framework (Shi et al, 2019;Li et al, 2022;Ma et al, 2022;O'Connell et al, 2022;Power and Berenson, 2022;Rodriguez et al, 2022).…”
Section: Figure 16mentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that DDP has significantly better convergence rates compared to sequential quadratic programming (SQP) methods. Teng et al [18] further improved the convergence performance of DDP for matrix groups by designing the control objective in its Lie algebra. Both of these approaches [13], [18] formulate the trajectory optimization on matrix Lie groups in an unconstrained framework.…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…Teng et al [18] further improved the convergence performance of DDP for matrix groups by designing the control objective in its Lie algebra. Both of these approaches [13], [18] formulate the trajectory optimization on matrix Lie groups in an unconstrained framework. In order to address this limitation, Liu et al [14] extended the work [13] by imposing SO(3) pose constraints.…”
Section: Introduction and Related Workmentioning
confidence: 99%